Vehicular communications for smart cars protocols, applications and security concerns - Chowdhury, Niaz, 1984-; Mackenzie, L. M. (CRC Press, 2022)
This book covers a wide range of topics from the smart transportation domain. It discusses protocols, applications and security concerns in various vehicular networks using examples and easy-to-understand figures. The first four chapters focus on vehicular network protocols and applications, while the remaining four chapters incorporate security, trust and privacy issues with examples from real-life cases. The book concludes with a vision of what to expect in the near future and will be an invaluable resource for anybody interested in this nascent technology and its variegated applications. Dr. Niaz Chowdhury is a postdoctoral research associate at the Knowledge Media Institute, the Open University in England. Dr. Lewis M. Mackenzie is a senior lecturer in computing science at the University of Glasgow.